Numerical Simulation of Heat Injection Extraction in Fractured Natural Gas Hydrate Reservoir - Luanluan XUE; Rui PENG (南方能源建设)
[Introduction] Natural gas hydrate is a clean energy source with great exploitation value, but the insufficient heat supply in the late stage of hydrate extraction leads to a low gas production rate. Reservoir modification can significantly increase hydrate reservoir permeability and improve heat transfer efficiency. Based on this, the effect mechanism of the gas production rate of fractured hydrate reservoirs under heat injection extraction mode after fracturing is analyzed. [Method] Hydrate reservoir after fracturing modification was taken as the research object in this paper, and a numerical model of thermo-hydro-chemical was established to simulate and analyze the effects of heat injection temperature, fracture aperture, and heat injection velocity on the gas production rate of hydrate reservoir, and then the orthogonal design of heat injection parameters was carried out. [Result] The results show that the effect of heat injection temperature, heat injection velocity, and fracture aperture on gas production rate can be divided into three stages in the process of fractured hydrate heat injection extraction, and the higher the heat injection temperature, heat injection velocity, and fracture aperture, the higher the gas production rate of hydrate reservoir. The orthogonal analysis of heat injection parameters shows that the heat injection temperature has a significant effect on the peak gas production rate, followed by heat injection velocity, and the fracture aperture has the least effect. [Conclusion] In this paper, the effect mechanism of gas production rate in heat injection extraction of a hydrate reservoir with a single fracture is clarified, and the efficiency of hydrate extraction is qualitatively evaluated, which provides some ideas for hydrate extraction in situ.